Validity and Reliability of the Persian Version of the Tinnitus and Hearing Survey Questionnaire - Seyed Alireza Alavi Dehkordi; Maryam Ramezani; Mohanna Javanbakht; Mohsen Vahedi (Auditory and Vestibular Research)
Background and Aim: Hearing loss often coexists with various comorbidities and is commonly accompanied by tinnitus. Patients frequently report both tinnitus and hearing difficulties, posing challenges in distinguishing between the two complaints. This study aimed to assess the validity and reliability of the Persian version of the Tinnitus and Hearing Survey (THS) for distinguishing between tinnitus and hearing problems. Methods: A psychometric study involved 100 participants aged 18–60, categorized into four groups based on hearing status and tinnitus presence. The Persian translation of a questionnaire underwent content and face validity assessments. Convergent validity for tinnitus and sound tolerance sections was evaluated using the Tinnitus Handicap Inventory (THI) and Hyperacusis Questionnaire (HQ) respectively, while pure-tone average assessed hearing section validity. Construct validity was confirmed via confirmatory factor analysis, and internal consistency and test-retest reliability were assessed using Cronbach’s alpha and Intraclass Correlation Coefficient (ICC) respectively. Results: The Persian version had strong face and content validity, with Cronbach’s alpha values of 0.82 for tinnitus, 0.90 for hearing, and 0.80 overall. The ICC values for the tinnitus, hearing, and sound tolerance sections were 0.8, 0.83, and 0.82. Convergent validity using the THI and HQ scores were reported 0.76 and 0.6, and the correlation value of the THS score with the PTA was 0.82. Confirmatory factor analysis confirmed a good 2-factor structure of the THS. Conclusion: The Persian THS is a valid and reliable tool for separating tinnitus from hearing problems in Persian-speaking people.